Applicability of a Hall Sensor in Directional Ground Fault Protections of MV Cable Networks with No-Effective Earthing - Habrych, Marcin; Miedzinski, Bogdan; Wang, Xin (Elektronika ir Elektrotechnika, 2016)
Paper presents and discusses results of analysis and research on the possibility of use of the Hall sensor as measuring element in directional ground fault protection. The considerations have been carried out for the new balance transformer structure with magnetic shielding. Its applicability has been confirmed by tests under real ground faults in MV networks of 6 kV and 20 kV with no-effective earthing. On the basis of the investigated results appropriate practical conclusions have been formulated.DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16339